2015
DOI: 10.1016/s0924-9338(15)30370-9
|View full text |Cite
|
Sign up to set email alerts
|

Was the Alcohol Psychoses Decline in Russia Attributable to Alcohol Control Policy?

Abstract: IntroductionSince 2003, Russia has experienced steep decline in alcohol psychoses incidence rate (APIR) and a parallel downward trend in the population drinking, driven mainly by a decrease in vodka (spirits) consumption. A coincidence in these trends allows us to hypothesize that the reduction in the APIR during recent decade might be attributed to the shift in the structure of consumption from vodka towards beer as a result of alcohol policy reforms.ObjectivesIn this study we will test the hypothesis of beve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Research from Russia has indicated that low-income groups of the population and heavy drinkers in Russia are likeliest to consume unrecorded alcohol, and this effect is especially evident during the economic crisis [8]. It is, however, unclear how much of the increase in unrecorded alcohol consumption in Russia was driven by alcohol policy measures and how much was an effect of the economic downturn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research from Russia has indicated that low-income groups of the population and heavy drinkers in Russia are likeliest to consume unrecorded alcohol, and this effect is especially evident during the economic crisis [8]. It is, however, unclear how much of the increase in unrecorded alcohol consumption in Russia was driven by alcohol policy measures and how much was an effect of the economic downturn.…”
Section: Discussionmentioning
confidence: 99%
“…In January 2010, the minimum price on vodka was introduced. Most importantly, excise tax rates on vodka in Russia have been increased [8]. Further, new set of amendments to the 171 Federal Low were adopted in 2011 [9].…”
Section: Introductionmentioning
confidence: 99%
“…A coincidence in the vodka consumption and mortality trends allows several experts to hypothesize that the reduction in the number of alcohol poisoning deaths during the last decade might be attributed to the implementation of the alcohol policy reforms, which increased government control over the alcohol market by raising taxes and restricting sales [2,40,41]. In his recent study [42] concluded that the implementation of alcohol policies was responsible for a decline in deaths due to alcohol poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Russia has one of the highest incidence of alcoholism in Europe [2], which may be explained by high overall alcohol consumption and prevalence of binge drinking of vodka [3][4][5][6]. Currently, there are approximately 5 million alcoholics (alcohol dependent individuals) in Russia, and the number of heavy drinkers is three to four times that number [2].…”
Section: Introductionmentioning
confidence: 99%
“…Most experts agree that the affordability of vodka is one of the most important predictor of the dramatic fluctuations in Russian mortality during the last decades [3][4][5][6]15]. There are, however, suggestions that heavy drinkers are less responsible to prices compared to the general population [16].…”
Section: Introductionmentioning
confidence: 99%